33rd AIAA Applied Aerodynamics Conference 2015
DOI: 10.2514/6.2015-2426
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Flow Control over Aerodynamic Bodies using Phased Array Vectored Synthetic Jet Actuation

Abstract: An experimental investigation into the flow control capabilities of synthetic jet actuators (SJAs) was performed. An array consisting of two synthetic jet actuators was designed and fabricated. The effects of vectoring an array on streamline location and pressure distribution were studied using Particle Image Velocimetry (PIV) and static pressure measurements. Three different bodies were tested: a flat plate, a two-dimensional cylinder representative of a bluff body, and a modified two-dimensional NACA 0018 ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Meanwhile, the synthetic jet actuator is usually small in scale, and the formed vortex ring has a high turbulence, moves at a faster velocity, and has a smaller volume. As such, these systems are widely used for drag reduction, heat transfer enhancement, and mixing control 31–34 . In VRPVs, owing to the need for a large air supply distance and ventilation flow rate, the formed vortex ring should have a considerable velocity and volume.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the synthetic jet actuator is usually small in scale, and the formed vortex ring has a high turbulence, moves at a faster velocity, and has a smaller volume. As such, these systems are widely used for drag reduction, heat transfer enhancement, and mixing control 31–34 . In VRPVs, owing to the need for a large air supply distance and ventilation flow rate, the formed vortex ring should have a considerable velocity and volume.…”
Section: Methodsmentioning
confidence: 99%
“…As such, these systems are widely used for drag reduction, heat transfer enhancement, and mixing control. [31][32][33][34] In VRPVs, owing to the need for a large air supply distance and ventilation flow rate, the formed vortex ring should have a considerable velocity and volume. Therefore, in view of characteristics of (a) and (b), this study proposes a vortex ring generator that uses a pneumatic device to drive a piston.…”
Section: High Ventilation Efficiencymentioning
confidence: 99%
“…In real world applications, it is SJ arrays that are usually implemented instead of single SJs. Using two slot SJ actuators, Hasnain et al [19] found that the point of flow separation on a two-dimensional (2D) cylinder can be delayed by 20% at specific phase difference between the two actuators. Zhao et al [20] confirmed that two slot SJ actuators generally have better performances than single SJ in delaying flow separation on a 2D airfoil.…”
Section: Introductionmentioning
confidence: 99%